Picture-Winged Fly, Delphinia picta (Fabricius) (Insecta: Diptera: Ulidiidae (=Otitidae)) - Howard V. Weems, Jr. (EDIS)
EENY-380, a 3-page fact sheet by H. V. Weems, is part of the Featured Creatures collection. It describes the synonymy, distribution, identification, life history and habits, and hosts of this native fly which is often confused with important fruit fly pests. Published by the UF Department of Entomology and Nematology, July 2006.